The Monitoring of Triphenylmethane Dyes in Aquaculture Products Through the European Union Network of Official Control Laboratories. (27th November 2019) - Verdon, Eric; Bessiral, Melaine; Chotard, Marie-Pierre; Couëdor, Pierrick; Fourmond, Marie-Pierre; Fuselier, Régine; Gaugain, Murielle; Gautier, Sophie; Hurtaud-Pessel, Dominique; Laurentie, Michel; Pirotais, Yvette; Roudaut, Brigitte; et al.
Abstract: Aquaculture has been the fastest growing animal production industry for the past four decades, and almost half of the fish eaten in the world are now farmed fish. To prevent diseases in this more intensive aquaculture farming, use of therapeutic chemicals has become a basic choice. The monitoring of malachite green, a triphenylmethane dye and one of the oldest and widely used chemicals in fish production, has gained more interest since the mid 1990s when this substance was finally proven to be toxic enough to be prohibited in seafood products destined for human consumption. The enforcement of the European Union (EU) regulation of this banned substance along with some other triphenylmethane dye congeners and their metabolites in its domestic production and in seafood imports was undertaken through the National Residue Monitoring Plans implemented in nearly all of the 28 EU member states. The reliability of the overall European monitoring of this dye contamination in aquaculture products was assessed by using the results of proficiency testing (PT) studies provided by the EU Reference Laboratory (EU-RL) in charge of the network of the EU National Reference Laboratories (NRLs). The proficiency of each NRL providing analytical support services for regulating dye residues was carefully checked during three PT rounds. In the process, the analytical methods developed and validated for this purpose have gradually been improved and extended over the last two decades.